ANALISIS PELAKSANAAN SISTEM INFORMASI PEMASARAN DALAM MENUNJANG PENGEMBANGAN ACARA DI TVRI STASIUN JAWA BARAT DAN BANTEN - Sri Fadilah (Program Magister Akuntansi Unsyiah, 2008)
TVRI is a broadcasting television company that gives communication services and the outputs are programs whether on air or off air in good quality and excellence. The aims of this research are to get information about the application of marketing information system in PT TVRI of West Java and Banten stations, and to know the application of programs development, and also to get information about marketing information system in supporting programs development in PT TVRI of West Java and Banten stations. This research used case study method and descriptive method analysis. The technique of data collecting in this research was by observation, questioner, interview, and documentation. From the results, we can conclude that the implementation of marketing information system in TVRI of West Java and Banten stations is adequate and good enough for programs development. Even though it still has weakness. This weakness is expected to become the consideration for TVRI of West Java and Banten stations in executing the development of marketing information system to support programs development. Keywords : Marketing Information System, Programs Development